PERSONAL QUALITIES OF BRILLIANT SURGEONS: A MYTH OR REALITY - Haroon Sabir Khan (Army Medical College Rawalpindi, 2018)
Objective: To explore the qualities of brilliant surgeons that makes them distinctive. Study Design: A qualitative exploratory study. Place and Duration of Study: The study was conducted in Armed Forces Hospitals, Rawalpindi, from Jan to Jul 2017. Material and Methods: A purposive sampling technique was applied for in-depth, semi-structured interviews of 19 members (ten surgeons, six anesthesiologists and three operation room assistants) having experience of surgical environment for more than 20 years in different institutions. Computer Assisted Qualitative Data Analysis Software (CAQDAS) was employed for thematic data analysis using software NVIVO 11 Pro. Results: Study participants reported observation of distinctive personality characteristics of a few surgeons hitherto termed as “brilliant”. Multifaceted aspects of their personality were identified and categorized into five major themes: mental, psychological and emotional, social, mechanical, and structural strength. The first three themes were found to be common among brilliant achievers in all other professions as well, however, the mechanical and structural strength domains were considered to have unique and substantial bearing on the achievement of brilliance in surgery. Conclusion: A category amongst the surgeon has been identified and termed as “brilliant”. These brilliant surgeons were gifted in five domains of their personality with a distinct set of qualities which made them outclass their contemporaries.